ظاهرة التصغير في كتاب سيبويه وأبعادها النظرية والدلالية والجمالية - يحيا, مالك (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يحاول هذا البحث أن يوضح ظاهرة التصغير في كتاب سيبويه، لذلك درس معنى التصغير وأهميته في رد الحروف إلى أصولها، وتناول مجموعة القواعد والأصول التي جرت عليها العربية في التقعيد ، فظهرت مظاهر الأصل والفرع، والقياس والتعليل والإفراد واضحة في القضايا التي ناقشها البحث، كما تناول البحث المعنى الرئيس للتصغير وهو التقليل، وأثر دلالة الكلمة أو نوعها على كيفية تصغيرها ... ، وهل الدلالة تسمح بالتصغير أو لا تسمح ؟، وبحث أخيراً تفضيل صيغة على أخرى في التصغير، وأسس استحسانها التي تعتمد على معايير دلالية أو صرفية، أو على معيار السماع والشيوع . This paper aims at investigating the extent to which the different types of diminution explained in Sibawayh's Book support the linguistic, semantic, aesthetic, and intellectual aspects. In this paper, the meaning and the significance of diminution are studied in connection with establishing the letter's etymologies. The study highlighted that the intellectual aspect is grounded on a set of rules and standards operative in Arabic, and how this aspect is highly featuring in the various cases presented here. In particular, the study focused on the semantic side of diminution, insofar as it is associated with the idea of smallness or belittling. The analysis revealed that the grammatical category of any given word determines the diminutive form to be adopted, e.g. masculine vs. feminine, or being a noun, adjective a summative or non summative plural, person or neuter, and whether or not the word permits undergoing the process of diminution. The study closes by discussing the aesthetic value which manifests itself in opting for one particular lexical construction but not another, especially when the two constructions can be used. The choice here does seem to depend on certain phonetic, semantic, auditory, or intellectual standards.